2016
DOI: 10.1103/physrevb.94.235147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface symmetry breaking on the magnetism, collapsing, and three-dimensional dispersion of the Co pnictidesACo2As2(A=Ba, Sr

Abstract: We use angle-resolved photoemission (ARPES) to study the three dimensional (3D) electronic structure of Co pnictides ACo2As2 with A=Ba, Sr, Ca or a mixture of Sr and Ca. These compounds are isostructural to Fe based superconductors, but have one more electron in the Co 3d orbitals. Going from Ba to Ca, they become more and more 3D, eventually forming a "collapsed" tetragonal phase, where the distance between CoAs layers is markedly reduced. We observe with ARPES the periodicity of the electronic structure as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…4 by zooming on the band dispersion near E F , these two bands fit the calculations better after renormalizing the LDA bands by a factor of 1.35. This factor is far from that observed in the Fe-based superconductors and more consistent with the renormalization found in BaCo 2 As 2 [10,11], which corresponds to a d 7 filling. From that perspective, the case of BaCr 2 As 2 is thus not symmetrical to BaFe 2 As 2 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…4 by zooming on the band dispersion near E F , these two bands fit the calculations better after renormalizing the LDA bands by a factor of 1.35. This factor is far from that observed in the Fe-based superconductors and more consistent with the renormalization found in BaCo 2 As 2 [10,11], which corresponds to a d 7 filling. From that perspective, the case of BaCr 2 As 2 is thus not symmetrical to BaFe 2 As 2 .…”
Section: Resultssupporting
confidence: 81%
“…It was established theoretically that the strength of the electronic correlations in these materials is tuned by the filling of the 3d shell in presence of a large Hund's coupling [2][3][4][5][6][7]. Accordingly, angle-resolved photoemission spectroscopy (ARPES) studies report that the band renormalization factor 1/Z decreases monotonically upon filling the 3d shell: 1/Z = 3 in BaFe 2 As 2 (d 6 ) [8] (consistent with density functional theory (DFT) + dynamic mean-field theory (DMFT) calculations [9]), 1/Z = 1.4 in BaCo 2 As 2 (d 7 ) [10,11], 1/Z = 1.1 in SrNi 2 As 2 (d 8 ) [12], and 1/Z = 1 in BaCu 2 As 2 (d 10 ) [13]. Within this framework, the electronic correlations should evolve similarly as a function of band filling with respect to the half 3d shell case (d 5 ).…”
Section: Introductionmentioning
confidence: 79%
“…[12][13][14][15] There has been extensive work on the cobalt analogues to "122" iron pnictides, ACo 2 Pn 2 , with various interlayer alkali or alkali-earth cations (A). [16][17][18][19][20][21][22][23] The observed magnetism in these pnictides was largely tuned by size and electronic effects from changing the CoPn layer distances.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we observe that the hole bands are moved 300-400 meV below the E F compared to the hole bands crossing E F in the AFe 2 As 2 compounds. Here in case of ACo 2 As 2 , the rigid-band-like shift in the band structure results in the appearance of a small electron pocket at the Γ point [49][50][51]. Moreover, we find that the bands in the vicinity of E F are reasonably flat, which are responsible for high intensity peak in the density of states (DOS) at E F and important to understand the physical properties of these ACo 2 As 2 materials.…”
Section: Introductionmentioning
confidence: 72%
“…Notably, there have been many reports on the structural and magnetic properties of these ACo 2 As 2 compounds [34][35][36][37][38][39][40][41][42][43][44]; however, detailed ARPES studies are very few [49][50][51] and not reported for EuCo 2 As 2 . Therefore, further investigations of the band structure and FSs of ACo 2 As 2 and comparison with the AFe 2 As 2 parent compounds are desired to shed light on the pairing mechanism of Fe-based superconductors.…”
Section: Introductionmentioning
confidence: 99%